'We had the most wonderful times': seaside nostalgia at a British resort. Issue 2 (3rd May 2016) - Jarratt, David; Gammon, Sean
ABSTRACT: Morecambe is a traditional British seaside resort that experienced a dynamic ebb and flow of visitors. It still attracts visitors, many of whom are from the North of England and in the second half of their lives. The experiences of such traditional seaside markets have not been examined as carefully by academics in recent years as one might assume; all too often this subject falls in the gap between serious academic study and popular culture. Instead, this paper attempts to gain an understanding of this seaside experience, and is based around 10 semi-structured interviews with 55–74-year-old repeat visitors of North of England to Morecambe. It considers their nostalgic connection and reaction to the resort, which emerged as a significant element of visitor experience. The seaside is considered timeless by these visitors and facilitates a reverie through which one can temporarily revisit a past which is populated by childhood memories of family members. The resort allows visitors to fleetingly transcend time, through immersion in the unchanging resort with its timeless seascape. This reconnection with the past highlights a dissatisfaction with the present which hinges on the loss of childhood. Yet nostalgia also allowed for a positive re-telling of the past which underpinned family narratives and contributed to the cross-generational appeal of the beach.